Behavior of Ultrafast Annealed Advanced High Strength Steels Under Static and Dynamic Conditions - Castro-Cerda, F (Elsevier Ltd, 2020)
Ultrafast annealing (UFA) is considered a feasible alternative processing route for third-generation advanced high strength steels (AHSSs). In fact, significant grain refinement occurs in low carbon steels (0.1 wt%) when heating rates (example, 1000 K/s) considerably higher than the conventional heating rates are applied. Additionally, high heating rates result in multiphase microstructures containing ferrite, retained austenite, and martensite/bainite. The mixture of structural constituents is induced by carbon gradients resulting from the short time available for diffusion during ultrafast annealing of the steel. Quasi-static and high strain rate tensile tests, with strain rates ranging from 0.0033 s−1 to 600 s−1, revealed that the tensile strength of both conventional and UFA samples increases with increasing strain rates, whereas the strain to fracture decreases. However, compared with the conventionally heat-treated samples (heating rate: 10 K/s), the UFA samples exhibited less ductility deterioration at high strain rates. The samples were investigated using light optical microscopy, scanning electron microscopy, electron backscatter diffraction (EBSD), and X-ray diffraction. The results indicated that the improved tensile properties of the UFA steels (compared with those of the conventional steels) resulted mainly from the presence of retained austenite (up to 5%) in conjunction with a lower carbon martensite/bainite fraction. Owing to adiabatic heating associated with dynamic conditions, the stability of retained austenite shifted to higher strain values than those encountered under static conditions. The TRIP effect of the UFA samples appeared at higher strain values than in the conventionally heat-treated samples. The delayed transformation is considered essential for realizing improved preservation of the deformation capacity and, in turn, improved crashworthiness. © 2020 Elsevier B.V.